Compressive Strength Analysis of a Steel Bolted Connection under Bolt Loss Conditions - Grzejda, Rafal; Perz, Rafal (Communications - Scientific Letters of the University of Zilina, 2022)
The aim of the study is the numerical analysis of a bolted connection under the conditions of loss of bearing capacity of some fasteners in this connection. The joined plates in the connection were made of the 3D finite elements, while the fasteners were treated as hybrid models consisting of rigid heads and nuts and flexible beams between them. A model of unilateral contact with friction was used between the joined plates. The bolted connection was first preloaded according to three different tensioning sequences and with a normalised force. After all the bolts were tensioned, the selected bolts were removed, simulating bolt damage under connection loading conditions. The connection was tested for external compressive loads up to 210 kN. The effect of the loosening of the connection on the load in the remaining bolts at the stage of the connection operation was investigated.
Keywords: structural health monitoring; bolted connection; preload; fastener damage; finite element method